Tinjauan Lama Waktu Penyediaan Rekam Medis Rawat Jalan Di Rumah Sakit Anna Medika Bekasi - Winda Febriarini; Puteri Fannya; Nanda Aula Rumana; Noor Yulia (Yayasan Literasi Sains Indonesia, 2022)
In the provision of medical record files in hospitals, it is one indicator of patient satisfaction whose time has been determined in accordance with the hospital's minimum service standards, the standard for the time of providing medical record documents for outpatient services is less than or equal to 10 minutes. 10 minutes), while the time for providing inpatient medical record documents is less than or equal to 15 minutes ( 15 minutes). The purpose of the study was to determine the length of time for providing outpatient medical records at Anna Medika Hospital Bekasi. The research method uses a descriptive method with a quantitative approach, the population of outpatient medical record files visiting the hospital, the sample studied is 106 files, through observation, interviews and time measurement records in the timely provision of medical records so that researchers get research results. The results of the study found that 59 (55.66%) medical records were provided on time and 47 (44.34%) medical records were not provided on time. Factors causing the length of time of provision > 10 minutes are errors in storing medical records, full storage shelves, lack of competence of medical record officers. Suggestions can improve the quality of service and the speed of time for providing medical records and holding standard operating procedures (spo) regarding the provision of medical records.